Die Allegorie der Austria Die Entstehung des Gesamtstaatsgedankens in der österreichisch-ungarischen Monarchie und die bildende Kunst - Krasa-Florian, Selma (2007)
The intention of this paper is to give a correct inside in the review of the discussed periods. It tries to achieve this by using the means of Art History and Political History to get an exact inside. The allegorical representation of the Austria in this case is the means to get it. It stands for the specific aspects of the time, so for instance the dynastic Austria with the crown of Emperor Rudolph II. meaning the predominance of the ruling Habsburgs, the civic Austria with the mural crown showing the ideas of the middle class, especially in the German speaking parts of the country, with the acceptance of the predominance of the state over the ruler, according to Hegel, or also the victorious Austria with the laurel wreath as a symbol of the conquest of the revolution of 1848. The Habsburg monarchy including many different nations was the proper breeding ground of dissatisfaction and diversified nationalistic ideas. So the representation of the Austria is an important means of showing these ideas. The periods the paper is working on are roughly speaking starting with the time of the beginning of the position of the monarchy as one of the ruling powers of Europe until her dissolution and the end of World War I. Different aspects of art history are also dealt with. So for example the 13 portraits of Habsburg rulers in the Museum Nordico at Linz, which are positioned in the time of Rudolph II. and mark the beginning of the representation of the allegory of the Austria, or the designs for monuments by Otto Wagner which are dealt with in the many books on this architect only as a side issue, whereas they are a very important part of wagners work and show his national feelings, towards his fatherland. It is furthermore interesting to look at the nationalistic problems shown in this paper and compare them with contemporary Europe and the overcoming of them. These ideas are not new, the date back to the 19th and especially the beginning of the 20th century when the Monarchy tried to overcome the problems with the slogan of Großösterreich (Greater Austria). During World War one followed the idea of Mitteleuropa (Central Europe) including Turkey and the institution of a Polish State to hold off revolutionary Russia